2018
DOI: 10.4055/cios.2018.10.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Relationships between Muscles Overlying Distal Transverse Carpal Ligament and Thenar Motor Branch of the Median Nerve

Abstract: BackgroundThe purpose of the current study is to investigate anatomical relationships between the muscle overlying the distal transverse carpal ligament (TCL) and the thenar motor branch of the median nerve.MethodsOf the 192 wrists that underwent open carpal tunnel release, a muscle belly overlying the TCL was observed on the distal margin of TCL in 25 wrists and ligament exposure could not be achieved without transection of it. We recorded surgical findings of these 25 wrists. The origin of the recurrent moto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 10 publications
0
10
0
4
Order By: Relevance
“…10 The overlying muscle on the distal transverse carpal ligament has been reported as an anatomic variation and occurs in 13-36% of cases. 16,17 Jegal et al mentioned that the presence of this overlying muscle indicated that the thenar motor branch originated from not only the radial side but also the anterior or ulnar side. 17 They warned of the possibility of thenar motor branch injury during transverse carpal ligament transection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 The overlying muscle on the distal transverse carpal ligament has been reported as an anatomic variation and occurs in 13-36% of cases. 16,17 Jegal et al mentioned that the presence of this overlying muscle indicated that the thenar motor branch originated from not only the radial side but also the anterior or ulnar side. 17 They warned of the possibility of thenar motor branch injury during transverse carpal ligament transection.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Jegal et al mentioned that the presence of this overlying muscle indicated that the thenar motor branch originated from not only the radial side but also the anterior or ulnar side. 17 They warned of the possibility of thenar motor branch injury during transverse carpal ligament transection. 16,17 In our experience, we did not observe the thenar motor branch in the overlying muscle during separation.…”
Section: Discussionmentioning
confidence: 99%
“…Among 272 subjects whose carpal tunnels were examined bilaterally, Green and Morgan 5 noted that less than one-third of subjects had a purely unilateral anomalous TMB. More recently, Jegal et al 6 assessed 192 open carpal tunnel releases, finding 25 wrists with muscle overlying the TCL—four of which were bilateral cases. Fourteen of the 25 were found to have an ulnar course of the TMB that tracked into this hypertrophic muscle overlying the TCL.…”
Section: Discussionmentioning
confidence: 99%
“…CTS is the most common pathology among the peripheral nerve lesions [1][2][3]. Nowadays, it is increasingly seen in persons who work with computers at desk [1][2][3][4][5]. CTS should be initially treated with medical and physical therapy modalities [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
“…Classical medical literature suggests longitudinal incision as the standard method [1][2][3]. Various techniques have been developed aiming at minimal skin incision concerning complications and healing problems [4,5].…”
Section: Introductionmentioning
confidence: 99%